Factors affecting Palestinians' intention towards environmental tax implementation - Shaheen, Mohammed M.S (Kuliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2016)
Pollution is increasing rapidly around the world, and its effects are becoming more and more pronounced. These effects are hazardous to human life. Some actual and expected effects of pollution have been addressed in several research papers. Approximately 47 billion ton of emissions are generated from the various sources of pollution, and 300,000 people are killed per year, 325 million humans severely affected, 4 billion inhabitants are vulnerable, half a billion humans are at extreme risk, and the losses of social welfare are valued at US$125 billion per year globally. This number is expected to increase to 70 billion ton of emissions in 2030, while the temperature of the earth is expected to increase by 2-4 degrees by the next century. Pollution is similar in Palestine as it is in other countries around the globe. This pressure is embodied in the sharp increase of emissions from diverse sources from 2006 to 2011. The potential effect of the pollution in Palestine could be seen in the increased spending on both environment and health, where it increased from US$62.5 million in 2011 to US$66.8 million in 2012, and increased from less than US$400 million in 2000 to greater than US$1.3 billion in 2013, respectively. In light of these facts, the researcher was motivated to elicit Palestinians intentions towards the implementation of environmental taxes as a potential tool to mitigate pollution. In order to achieve that goal, the research used several vehicles, namely the citizens' beliefs about the consequences of climate change, Palestinian beliefs about the potential impacts of the environmental tax, and their attitudes towards the implementation of environmental taxes. The Theory of Planned Behavior (TPB) forms the theoretical background of the study. This research was carried out in the West Bank in Palestine using an online survey. The study found that Palestinians are well aware of the consequences of climate change, and they believe that it will negatively affect not only their daily life, but is also detrimental to animals and plants. They believe that environmental taxes will help decrease pollution, and ultimately increase their quality of life. A positive attitude towards the implementation of environmental taxes among Palestinians was confirmed. Moreover, around 74.3 percent of the Palestinians intend to accept environmental tax as a new tax, and 69.5 percent of them intend to accept environmental tax as an increment to the current taxes if the revenue is to be used to tackle environmental degradation. Finally, gender, age, level of education, occupation, income, marital status, and the place of residence are the social, economic, and demographic factors that were utilized in this research as control variables. These control variables were found to not have any significant effect on Palestinians' intention towards the implementation of environmental taxes.